Retracted: How a Game Theoretic Approach Can Minimize the Cost of Train Passenger Services: An Intermodal Competition between Rail and Road Transport: The article was retracted by the editors of Collective Dynamics. The editors are in contact with the author. - Yangailo, Tryson (Collective Dynamics, 2023)
Retracted article.